Analisis Perubahan Fonem dalam Pelafalan Fonem Vokal dan Konsonan Bahasa Indonesia pada Dialek Jawa Timur - Azizan, Yoga Rifqi; Yonita Shelly Anggraeni; Moh. Ahsan Shohifur Rizal; Abdul Kholiq (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
This research aims to analyze phoneme changes in the pronunciation of Indonesian vowel and consonant phonemes in dialects in East Java. The method used in this research is a descriptive method with a quantitative and qualitative approach. This research was carried out online (on the network). The technique used was random sampling or random sampling with a sample size of 25 from the community in East Java. Indonesian is the national language and has spelling rules that its speakers must use. Speakers from Sabang to Merauke definitely have different dialects in each region, including in East Java Province. East Java Province contains many ethnic groups. Every ethnic group has a culture or custom that is different from other ethnic groups, both in actions and in the way they say it. Therefore, with the many ethnic groups in East Java, each region also has differences in the pronunciation of words, both vowels and consonants, or what could be called dialect. Problems regarding changes in sound or pronunciation in Indonesian are included in the realm of phonological research. This research is based on the emergence of changes in pronunciation phonemes in the use of Indonesian. The focus of this research is phoneme changes in certain words in Indonesian in the East Javanese dialect. Keywords: changes in phonemes, pronunciation, dialect